Synthesis and characterizations of zeolite catalyst from natural quartz in Kurdistan Region-Iraq - A.Smail, Heman (Sulaimani Journal for Pure and Applied Sciences, 2021)
In this work a cheap and an affordable natural quartz powder was used as a silica source, converted to a sodium silicate solution, for synthesising the low silica kind X (LSX) with process of hydrothermal the zeolite LSX with the formula Na73K22[Si97Al95O384] . 212H2O. The synthesized zeolite with the types cations of K and Na, considered as NaK-LSX, the best time to complete crystallization was 3.0 h, was features of the agent performing Fourier transforms infrared spectroscopy (FT-IR) and X-ray diffraction (XRD), that affirmed the synthesis effectiveness. Images of field emission scanning electron microscope (FE-SEM) in the (NaK-LSX) illustrated particles of multi-faceted spherulite composing polycrystal particles that have various measures as well as particles of small amorphous. Measuring of the average pore size and, volume of total pore for sample utilizing the “Barrett-Joyner-Halenda (BJH)”technique, the particle magnitude spread over an area of NaK-LSX about 67nm, and nitrogen adsorption is indicating an area of surface about 732.29 m2/g applying “Brunauer-Emmett-Teller (BET)” technique. The synthesizes zeolite (LSX) may have different kind of usages including, industrial applications as a gas or vapour adsorption, separation and as a catalyst.In addition they may also be used as a selective adsorbent in purifying polluted air.
Keywords: Natural quartz; NaK-LSX; zeolite; hydrothermal synthesis